2000
DOI: 10.1080/010503900424552
|View full text |Cite
|
Sign up to set email alerts
|

Double blind comparison of three hearing aid circuits with new hearing aid users

Abstract: This study was a double blind comparison of three types of hearing aid circuits: Class A linear peak clipping, Class D compression limiting and K-Amp wide dynamic range compression. Subjective ratings, speech perception tests, real ear measurements and questionnaire data were obtained from a group of 17 new hearing aid users with mild to moderate sensorineural hearing loss. The results indicate a similar performance for all three circuits. We saw no evidence of performance degradation due to saturation distort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…The study by Larson et al (2002) found significant differences on ratings of sound quality (effect sizes 0.16 to 0.47) and self-report questionnaire (no statistics reported), whereas no significant differences were reported for the self-report questionnaire used in the study by Hayes and Cormier (2000).…”
Section: Placebo Effects and Hearing Aid Trialsmentioning
confidence: 69%
See 1 more Smart Citation
“…The study by Larson et al (2002) found significant differences on ratings of sound quality (effect sizes 0.16 to 0.47) and self-report questionnaire (no statistics reported), whereas no significant differences were reported for the self-report questionnaire used in the study by Hayes and Cormier (2000).…”
Section: Placebo Effects and Hearing Aid Trialsmentioning
confidence: 69%
“…Boymans et al 1999;Ricketts & Dhar 1999), single-blinded † (Bille et al 1999;Boymans & Dreschler 2000;Wood & Lutman 2004), or double-blinded ‡ (Hayes & Cormier 2000;Larson et al 2002) methodology in comparing one type of hearing aid with another (i.e., aided A versus aided B performance). Note that the aforementioned studies were selected on the basis of a Google Scholar search with the key words "hearing aid trial," and on the availability of the full manuscript.…”
Section: Placebo Effects and Hearing Aid Trialsmentioning
confidence: 99%
“…These front ends are usually variations of compressive and nonlinear hearing aid amplifiers, and cannot generally be characterized by simple level-independent transfer functions [e.g. Hayes and Cormier, 2000]. Furthermore, IMEHD input transducers and their processors generally have programmable gains and frequency bandpasses and consideration of such variations would greatly complicate this report [e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Surprisingly, even some studies with participants having mild to moderate hearing loss have reported no adverse effects of peak clipping. Hayes and Cormier (2000) report no degradation in subjective ratings or speech perception for peak clipping relative to compression limiting. Stelmachowicz et al (1999) found an unusual preference for the peak clipping condition rather than the compression limiting, for clarity of speech in quiet presented at 80dB SPL, for 10-to 12-yr-old and 16-to 50-yr-old participants.…”
Section: Discussionmentioning
confidence: 81%